Biosynthesis of methyleugenol and methylisoeugenol in Daucus carota leaves: Characterization of eugenol/isoeugenol synthase and O-Methyltransferase. (March 2019) - Yahyaa, Mosaab; Berim, Anna; Nawade, Bhagwat; Ibdah, Muhammad; Dudareva, Natalia; Ibdah, Mwafaq
Abstract: Carrot ( Daucus carota subsp. sativus ) is a widely cultivated root vegetable of high economic importance. The aroma of carrot roots and aboveground organs is mainly defined by terpenes. We found that leaves of orange carrot cultivar also produce considerable amounts of the phenylpropenes methyleugenol and methylisoeugenol. Notably, methyleugenol is most abundant in young leaves, while methylisoeugenol is the dominant phenylpropene in mature leaf tissue. The goal of the present study was to shed light on the biochemistry and molecular biology of these compounds' biosynthesis and accumulation. Using the available genomic and transcriptomic data, we isolated a cDNA encoding eugenol/isoeugenol synthase (DcE(I)GS1), an NADPH-dependent enzyme that converts coniferyl acetate to eugenol. This enzyme exhibits dual product specificity and yields propenylphenol isoeugenol alongside allylphenol eugenol. Furthermore, we identified a cDNA encoding S -adenosyl-L-methionine:eugenol/isoeugenol O -methyltransferase 1 (DcE(I)OMT1) that produces methyleugenol and methylisoeugenol via methylation of the para -OH-group of their respective precursors. Both DcE(I)GS1 and DcE(I)OMT1 were expressed in seeds, roots, young and mature leaves, and the DcE(I)OMT1 transcript levels were the highest in leaves. The DcE(I)GS1 protein is 67% identical to anise t -anol/isoeugenol synthase and displays an apparent K m of 247 μM for coniferyl acetate. The catalytic efficiency of DcEOMT1 with eugenol is more than five-fold higher than that with isoeugenol, with K m values of 40 μM for eugenol, and of 115 μM for isoeugenol. This work expands the current knowledge of the enzymes involved in phenylpropene biosynthesis and would enable studies into structural elements defining the regioselectivity of phenylpropene synthases. Graphical abstract: The enzyme reaction leading to eugenol and isoeugenol formation catalyzed by Daucus carota (iso)eugenol synthase. Highlights: Eugenol/isoeugenol synthase and O -methyltransferase were identified from carrot. The recombinant phenylpropene synthase catalyzes the formation of both eugenol and isoeugenol. The recombinant eugenol/isoeugenol O -methyltransferase shows specificity towards phenylpropenes. Expression analysis suggests that the enzymes may play a role in eugenol/isoeugenol derivatives biosynthesis. Expression analysis suggests that the isolated genes are involved in phenylpropene biosynthesis in carrot.